2021
DOI: 10.2147/opth.s321344
|View full text |Cite
|
Sign up to set email alerts
|

Retropupillary Iris-Claw Intraocular Lenses: A Literature Review

Abstract: Retropupillary iris-claw intraocular lenses (ICIOLs) have been increasingly chosen by surgeons nowadays as a primary or secondary procedure of IOL implantation in eyes with insufficient capsular or zonular support. They have gained popularity due to their simple fast technique, favourable functional outcomes, and safety. The transition in the ICIOL fixation from prepupillary to a more biologically appropriate retropupillary position and change in the optic design from biconvex to convex–concave have provided b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 70 publications
0
23
0
8
Order By: Relevance
“…There is substantial evidence on the favourable short- and long-term outcomes of iris-claw IOLs in the treatment of IOL dislocation qualifying it as a valid alternative to scleral fixated or angle-supported IOLs. It is an efficient and safe surgical procedure 12 15 .…”
Section: Introductionmentioning
confidence: 99%
“…There is substantial evidence on the favourable short- and long-term outcomes of iris-claw IOLs in the treatment of IOL dislocation qualifying it as a valid alternative to scleral fixated or angle-supported IOLs. It is an efficient and safe surgical procedure 12 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Forlini indicated that retro pupillary iris claw lens is a suitable option for scleral-fixated or anglesupported lens [22]. Retropupillary iris claw lens implantation can safely and effectively correct aphakia without capsule support [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Forlini indicated that retro pupillary iris claw lens is a suitable option for scleral-xated or angle-supported lens (22). Retropupillary iris claw lens implantation can safely and effectively correct aphakia without capsule support (23,24).…”
Section: Discussionmentioning
confidence: 99%